2010
DOI: 10.1136/thx.2009.132670
|View full text |Cite
|
Sign up to set email alerts
|

Risk of invasive pneumococcal infections among working age adults with asthma

Abstract: Background Information about the risk of invasive pneumococcal infection (IPI) among adults with asthma is limited and inconsistent. To evaluate this association, a population-based caseecontrol study was conducted. Methods Cases of IPI (Streptococcus pneumoniae isolated from blood or cerebrospinal fluid) were identified through national, population-based laboratory surveillance during 1995e2002. To maximise exclusion of chronic obstructive pulmonary disease, the analysis was limited to patients aged 18e49 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 25 publications
4
78
0
4
Order By: Relevance
“…People with asthma have increased susceptibility to streptococcal infections, [13][14][15] increased carriage of bacterial pathogens identified by culture 16 and molecular techniques, 17 and impaired interferon and type 1 T helper cell responses to bacterial polysaccharides. 18,19 Viral infection impairs antibacterial innate immune responses 20 and increases bacterial adherence to bronchial epithelium.…”
mentioning
confidence: 99%
“…People with asthma have increased susceptibility to streptococcal infections, [13][14][15] increased carriage of bacterial pathogens identified by culture 16 and molecular techniques, 17 and impaired interferon and type 1 T helper cell responses to bacterial polysaccharides. 18,19 Viral infection impairs antibacterial innate immune responses 20 and increases bacterial adherence to bronchial epithelium.…”
mentioning
confidence: 99%
“…Various studies have shown that asthmatic patients have an increased risk of acquiring bacterial infections, such as induced by Haemophilus influenzae and Spn, which may cause asthma exacerbation [13,15,16]. At the same time, asthmatic patients exhibit more severe and long-lasting respiratory tract symptoms following viral infections [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, limited availability of L-arginine to iNOS due to increased Arg1 activity results in a deficiency of bronchodilatory and anti-inflammatory NO, while at the same time fostering AHR and L-ornithine-dependent airway fibrogenesis, thus suggesting an important role of Arg1-dependent altered NO metabolism in the development of allergic asthma [12,13]. However, limited availability of NO due to increased Arg1 activity may not only promote asthma progression but may also inhibit NO-dependent lung antibacterial immunity against, for example, pulmonary Streptococcus pneumoniae (Spn) infections [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre eles, pode-se destacar a expressão de fatores de virulência pela bactéria ou o desenvolvimento de uma resposta imune inata ineficiente por parte do hospedeiro (Weiser, 2010). Algumas condições predispõem às infecções pneumocócicas, como por exemplo a asma (Jounio et al, 2010;Klemets et al, 2010;Talbot et al, 2005) ou infecções virais, como a influenza (Mina;Mccullers;Klugman, 2014 (Ferreira et al, 2009;Lima et al, 2012;Lima et al, 2013;Oliveira et al, 2010). O controle da inflamação parece ser um componente importante tanto na proteção induzida pelas vacinas estudadas quanto nos mecanismos inatos de eliminação das bactérias do trato respiratório.…”
Section: Discussionunclassified